3 Dimensional Printing in Cardiology: Innovation for Modern Education and Clinical Implementation - Putrika Prastuti Ratna Gharini; Herianto Herianto; Nur Arfian; Ferdinandus Bayu Satria; Nur Amin (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Medical uses of three-dimension (3D) printing have advantages for many importances, such as tissue and organ fabrication, creation of prosthetics, and model structural anatomy. Visualization of 3-dimensional structure of heart for the importance of examination, management or education is not fully comprehensive describe toward the complexity of anatomical structure and also toward the illustration of medical procedure. The aim of this study was to identify the potential application of heart’s 3D printing for the enhancement of case understanding for doctor, medical students or residents and also for patient and its family. A normal model of heart is used in this research to stimulate next 3D object in cardiology area.We retrieved data from patients’ CT scan performed in Gadjah Mada University Hospital, Yogyakarta from December 2017 to March 2018. Our focus is on normal heart anatomy. Data from CT scan results are exported into Digital Imaging and Communications format (DICOM), then dimension measurement and threshold segmentation are performed using Mimics Medical 20.0 (Materialise) application. Finally the file must be exported into STL format due to final process to cut the desirable parts using Mesh editing application. After the final model has been done, then it will be printed by fuse deposition method to make a 3D object.The making and implementing 3D printingof heart model has many advantages for medical education especially for the doctor, medical students or residents and also for the patient and its family to be more aware on the condition of the heart. This study may stimulate another trial of using this technique into several heart abnormalities